Condensate Formation in Collisionless Plasma - Treumann, R. A.; Baumjohann, Wolfgang (Frontiers in Physics, 2021)
Particle condensates in general magnetic mirror geometries in high-temperature plasmas may be caused by a discrete resonance with thermal ion-acoustic background noise near mirror points. The resonance breaks the bounce symmetry, temporally locking the particles to the resonant wavelength. The relevant correlation lengths are the Debye length in the parallel direction and the ion gyroradius in the perpendicular direction.